Microcephaly in Infants: A Retrospective Cohort Study from Turkey - Gonca Keskindemirci; Öykü Özbörü Aşkan; Burak Selver; Alev Bakır Kayı; Gülbin Gökçay (Galenos Yayincilik, 2024)
INTRODUCTION: Microcephaly (MC) is a clinical finding mostly reflecting deficiency of brain growth. The aim of this retrospective cohort study was to assess risk factors and follow-up features of children with MC. METHODS: Children's personal health records (n=7580) followed between 2002 and 2020 in the Unit of a Well Child Clinic were assessed retrospectively. The case group comprised children with MC. MC was defined as head circumference (HC) standard deviation score (SDS) value ≤-2 SDS. Age and sex-matched children with normal HC were selected as the control group. RESULTS: Children with MC (n=49) had more disadvantaged sociodemographic characteristics, such as young maternal and paternal age and low maternal and paternal education. Breastfeeding was more common among controls (n=98). Resolution of MC was observed in 26 (53.1%) children with MC, whether it was mild (HC SDS between -2 and -2.9) or severe (HC SDS ≤3). Children with persistent MC had poorer developmental milestones than controls and cases with resolution. Sociodemographic features or developmental milestones in mild and severe MC did not differ. DISCUSSION AND CONCLUSION: These results suggest that the use of a definition of MC of ≤-2 SDS would be appropriate in order not to miss cases on follow-up. Greater sociodemographic equality may prevent some cases of MC. Further studies are needed evaluating socioeconomic factors on MC.